The impacts of global risk and US monetary policy on US Dollar exchange rates and excess currency returns - Kerstin Bernoth; Helmut Herwartz; Lasse Trienens (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
We examine the causal relationship between US monetary policy shocks, exchange rates and currency excess returns for a sample of eight advanced countries over the period 1980M1 to 2022M11. We find that the dynamics of the US dollar exchange rate is the main driver of currency excess returns. The exchange rate is significantly affected by US monetary policy shocks, where the persistence of this shock is important, as well as by an external shock. This external shock is strongly related to global risk aversion and the convenience yield that investors are willing to pay for holding US Dollar assets. A significant part of the response of excess currency returns is also expected, suggesting a violation of the UIP. Focusing only on the post-crisis period, the impact of both the external shock and the inflation targeting shock on exchange rates and currency excess returns disappears in the cross-section.
Keywords: E52; C32; E43; F31; G15; F41; 330; exchange rates; excess currency returns; uncovered interest parity; convenience yield; global financial cycle; global risk; monetary policy